The chronic lymphocytic leukemia international prognostic index predicts time to first treatment in early CLL: Independent validation in a prospective cohort of early stage patients. Issue 11 (8th August 2016) - Molica, Stefano; Shanafelt, Tait D.; Giannarelli, Diana; Gentile, Massimo; Mirabelli, Rosanna; Cutrona, Giovanna; Levato, Luciano; Di Renzo, Nicola; Di Raimondo, Francesco; Musolino, Caterina; Angrilli, Francesco; Famà, Angelo; et al.
Abstract : The chronic lymphocytic leukemia International Prognostic Index (CLL‐IPI) combines 5 parameters (age, clinical stage, TP53 status [normal vs. del(17p) and/or TP53 mutation], IGHV mutational status, serum β2‐microglobulin) to predict survival and time‐to‐first‐treatment (TTFT) in CLL patients. We performed an observational study in 337 prospectively collected, Binet stage A patients to validate the ability of the CLL‐IPI to predict TTFT in an independent cohort of early stage CLL patients. The CLL‐IPI score stratified Binet stage A patients into three subgroups with different outcome. Since the CLL‐IPI was originally developed to predict survival, we next investigated the optimal cut‐off score to predict TTFT in Binet stage A patients. Recursive partitioning analysis identified three subsets with scores of 0 ( n = 139), 1 ( n = 90), and ≥ 2( n = 108). The probability of remaining free from therapy 5 years after diagnosis was 85%, 67% and 46% in these three categories ( P  < 0.0001.; C ‐statistic:c = 0.72; 95% CI:0.58‐0.81). This optimized CLL‐IPI scoring for TTFT was subsequently validated in an independent cohort of Binet A patients from the Mayo Clinic ( n = 525). The ability of either original or optimized CLL‐IPI to predict TTFT was equivalent to other prognostic models specifically designed for this endpoint (2011 MDACC score and O‐CLL1 score). Although originally developed to predict suvival, the CLL‐IPI is useful for predicting TTFT in early stage CLL patients. Am. J. Hematol. 91:1090–1095, 2016. © 2016 Wiley Periodicals, Inc.